Biogeography and genetic diversity of clinical isolates of Burkholderia pseudomallei in Sri Lanka - Jayasinghearachchi, Himali S.; Corea, Enoka M.; Jayaratne, Kumari I.; Fonseka, Regina A.; Muthugama, Thilini A.; Masakorala, Jayanthi; Ramasinghe, Ravija YC.; De Silva, Aruna D. (PLOS Neglected Tropical Diseases, 2021)
Author summary Burkholderia pseudomallei is an important cause of community acquired pneumonia, septicemia and abscesses in Sri Lanka. The risk of infection is increased after flooding following heavy rainfall. Risk groups include rice farmers and rural populations engaged in subsistence cultivation in home gardens. Nationwide surveillance has been carried out since 2006 and the state public health system offers free diagnostics and free antibiotic therapy. The incidence of melioidosis in Sri Lanka has increased in tandem with increased awareness among clinicians. This study reports the genetic diversity among Sri Lankan B. pseudomallei clinical isolates and shows that some variably present genes are regionally distributed. The population is intermediate between Southeast Asia and Oceania. This may reflect its past geological history.